Histological evaluation of local application of collagen I and /or vascular endothelial growth factor (An experimental study in rats) - Rafal Rashid; Athraa Y Al-Hijazi (College of Dentistry/ University of Baghdad, 2015)
Background: The study was designed to evaluate the effect of local application of exogenous VEGF/collagen I separately and as a combination in socket healing. Sixty male Albino Wistar rats were subjected for a surgical tooth extraction of upper 1st molar of both sides (right side was considered as experimental site, while left be the control one, treated with 1µL of normal saline). The rats were scarified at 3, 7, 14, 28 days post extraction. Socket healing was histologically examined with immunohistochemistochemical localization of ALP&FGF2. Materials and Method: Sixty male Albino Wistar rats were subjected for a surgical tooth extraction of upper 1stmolar of both sides (right side was considered as experimental site, while left be the control one). The animals were divided into following groups according to the applicable of biomaterials. A. Control group the tooth socket treated with 1μL of normal saline B. Experimental group includes • Group I contains (20) rats, the tooth socket treated with 1μL of VEGF • Group II contains (20) rats the tooth socket treated with 1μL of collagen type I • Group III contains (20) rats, the tooth socket treated with 1μL of a combination of VEGF and collagen I. Results: At 28 days all groups show re-epithelization but in different thickness, and with newly bone apposition and with different maturity. For positive cells expressed ALP, VEGF group records a high mean values at 3, 14, 28 days periods and with high differences in comparison to other groups while control group reports a high mean value at 7 days . For positive cells expressed FGF2. Control group illustrates a high record for the mean of positive cells expressed FGF2 at 3,7days periods and with high differences in comparison to other groups, while combination group reports a high mean value at 14 days . Conclusion: Results, high lighted on the effect of local application of VEGF in extracted tooth socket that facilitate epithelization, while combination of (collagen and VEGF) shows a high mineralization zone.